From the Facebook Case to the DMA: Data Protection Considerations in EU Competition Policy - Jin,Lingzhi (2025)
This paper analyses the evolving nexus between personal data protection and antitrust law in the European Union’s digital economy, where personal data functions as a critical competitive resource. It explores how the German Fed-eral Cartel Office’s landmark 2019 decision against Facebook, which framed excessive data collection under non-compliant GDPR terms as an abuse of dominance, signalled a paradigm shift in antitrust enforcement. Unlike prior EU Commission approaches, this case directly linked data protection viola-tions to anti-competitive conduct, prompting judicial review by the Court of Justice of the European Union. Concurrently, the EU introduced the Digital Markets Act (DMA), establishing ex-ante rules for digital “gatekeepers” to curb data-driven market power. The DMA codifies rules from the German Facebook case decision, emphasising restrictions on exploitative data prac-tices. The CJEU’s 2023 ruling in Meta v. Bundeskartellamt affirmed that GDPR breaches may substantiate antitrust violations, validating the interplay between data protection and competition law. This study highlights the EU’s progressive data protection integration into antitrust frameworks, balancing market contestability with individual rights. It underscores the DMA’s role in institutionalising these synergies and addresses the challenges of regulating digital platforms where economic power and data sovereignty increasingly intersect. The findings illuminate the EU’s pioneering efforts to harmonise data governance and competition policy, offering insights for global regula-tory strategies in the digital age.
Keywords: German Facebook case; Meta v. Bundeskartellamt; Digital Mar- kets Act; General Data Protection Regulation; EU competition law; gate- keeper; digital markets; data; DMA